The dark hours [compact disc, unabridged] - Connelly, Michael, 1956- (Hachette Book Group, 2021)
There's chaos in Hollywood at the end of the New Year's Eve countdown. Working her graveyard shift, LAPD detective Renée Ballard is called to a scene where a hardworking auto shop owner has been fatally hit by a bullet in the middle of a crowded street party. Ballard quickly concludes that the bullet is linked to another unsolved murder--a case at one time worked by Detective Harry Bosch. At the same time, Ballard hunts a fiendish pair of serial rapists, the Midnight Men, who have been terrorizing women and leaving no trace. Determined to solve both cases, Ballard must go outside to the one detective she can count on: Harry Bosch.